DETERMINATION OF THE DIMENSIONS AND INDICATORS OF FOOD SECURITY IN INDONESIA: THE NATIONAL FOOD SECURITY BOARD-WORLD FOOD PROGRAM METHODOLOGY REVISITED - Edmira Rivani (Pusbindiklat - LIPI, 2012)
This study identifies the dimensions and indicators of food security and vulnerability that are relevant to bemonitored, and calculates a composite index based on food security and vulnerability indicators that represent thedimensions of food security based on the results of exploratory factor analysis. The method is as a new alternativeto the one used by the National Food Security Board (DKP)-World Food Program (WFP) in preparing the FoodSecurity and Vulnerability Atlas in Indonesia. The results show that the dimensions of food security are foodavailability, physical access, utilization, and social – economic aspects. The four dimensions explain 65,68%, ofthe total variance which indicates the models are fit. The indicators that should be included in the composite indexof food security are villages without access to road, female illiteracy, underweight children < 5 years, stuntingchildren < 5 years, household > 5 km from health facilities, and house hold without access to clean drinking water.This method may be considered as an alternative methodology in revising and updating the food security andvulnerability atlas that is regularly conducted by the DKP-WFP.